2006
DOI: 10.1089/acm.2006.12.421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Doses and High Homeopathic Potencies in Normal and Cancerous Human Lymphocytes: An In Vitro Isopathic Study

Abstract: High homeopathic potencies exhibit a biologic effect on cell cultures of normal primary lymphocytes. Cancerous lymphocytes (Jurkat), having lost the ability to respond to regulatory signals, seem to be fairly unresponsive to high homeopathic potencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…TNF-α up to 100x from 100 ng/ml elevated the level of H 2 O 2 in SK-N-SH neuroblastoma cells [30], arsenic of decimal and centesimal dilutions exerted effect in the rats [41], histamine dilutions ranging between 15-19c from 1 mg/ml inhibited human basophil degranulation [42]. In addition, normal and human leukemia T-lymphocytes responded to cadmium chloride at low doses (nM-μM; 0.2-200 ng/ml) [43]. Based on this it could be speculated, that the wound closure effect of the homeopathic remedy 0712–2 in NIH 3T3 fibroblasts may be due to the exerted properties of active ingredients at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α up to 100x from 100 ng/ml elevated the level of H 2 O 2 in SK-N-SH neuroblastoma cells [30], arsenic of decimal and centesimal dilutions exerted effect in the rats [41], histamine dilutions ranging between 15-19c from 1 mg/ml inhibited human basophil degranulation [42]. In addition, normal and human leukemia T-lymphocytes responded to cadmium chloride at low doses (nM-μM; 0.2-200 ng/ml) [43]. Based on this it could be speculated, that the wound closure effect of the homeopathic remedy 0712–2 in NIH 3T3 fibroblasts may be due to the exerted properties of active ingredients at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Beside this, immune stimulation by natural products has been attempted in various animal models and in human cancer patients as an adjunct to chemotherapy [41]. Pre-treatment with varying potencies of cadmium has been found to significantly increase lymphocyte viability after toxic challenge compared to control cells [42]. Oliveira et al [43] have recently revealed that highly diluted tinctures can efficiently decrease tumour necrosis factor-alpha (TNF-α) release and IFN-γ production in lipopolysaccharide (LPS)-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, effects of homoeopathic medicines in low doses and high potencies in normal and cancerous human lymphocytes were studied. 54 This study methodology involved pretreatment of cells with either high potencies (pool 15-20C) or low concentrations (nM-µM) of Cadmium. After 120 hours of medication, cells were exposed to Cadmium (8-80 µM).…”
Section: Dose Dependent Effects Of Homoeopathic Medicines On Cancer Cmentioning
confidence: 99%